Pertanggungjawaban Afiliator Atas Kerugian Customer Social Commerce - Tahalea, Hensly Daniel; Haliwela, Nancy Silvana; Labetubun, Muchtar Anshary Hamid (Faculty of Law, Universitas Pattimura, 2024)
The development of the times has made the internet not only a tool for communication but also a place for those who want to do business online. In accordance with Article 15, Paragraph (1) of the ITE Law, there are specific regulations regarding the electronic system organization, so everything related to the internet world must be carried out in accordance with this article. The electronic system organization must be conducted based on the contents of Article 15, Paragraph (1) of the ITE Law to avoid unlawful acts, which are regulated in Article 1365 of the Civil Code. Social commerce is a new development where sellers and consumers are connected through online social media. Social commerce has now become the answer for those who want to earn extra income with a side job that does not take much time, known as an affiliate. An affiliate is someone who works by promoting goods from sellers or sales. Regarding affiliates, there is a case where an affiliate with the initials IN experienced steroid poisoning from a product that he had already promoted. The legal research method used is normative juridical, which is carried out by studying legal principles and concepts, as well as legislation. The legal research method used refers to primary, secondary, and tertiary legal materials, with legislative and conceptual approaches. The research results show that there is a working relationship between the affiliate and the seller. Regarding trading activities through social commerce, an affiliate has the primary responsibility to ensure that the information provided to customers in marketing the products sold is clear and that the product conditions comply with Law No. 8 of 2008. The goal is to avoid legal risks or losses for customers. The affiliate’s liability in terms of compensating for losses depends on the content of the agreement between the affiliate and the product owner. Based on the affiliate’s liability, this liability can be classified as fault-based liability. Legal protection can be carried out by applying relevant laws and regulations as a preventive measure to ensure safety and legal compliance